QUENCY AND TYPES OF BODILY MEDICO-LEGAL INJURIES IN AN URBAN AREA - Ahmad, Iftikhar; Seema, Nighat; Shafi, Shagufta; Salim, Muhammad (Journal of Ayub Medical College Abbottabad, 2012)
Background: The primary objective of the study was to know the types and frequency of the bodily medico legal injuries in an urban setup of Abbottabad and compare it with that of rural study. Methods: Data was retrospectively collected by selecting 55 cases consecutively. Data of injury types was analysed. Results: The number of injured males in this study was 44 (80.0%), while the females were 11 (20.0%). The most common types of injuries were others (50.9% among males and 14.5% among females). Conclusions: Our study shows relatively true picture of frequency and types of injuries. It was observed that male population is more prone to violence than females owing to the conservative life style of women in our societies both rural and urban. Keywords: bodily medico-legal injuries, Shajja